THE CONTRIBUTION OF THE RUSSIAN ETHNOGRAPHER AND ORIENTALIST VLADIMIR PETROVICH NALIVKIN TO SCIENCE IN CENTRAL ASIA - Toshtemirov A. M. (Modern American Journals, 2025)
This article discusses the contribution of the Russian orientalist and ethnographer V.P.Nalivkin to the development of Central Asian and world science, who participated in the military campaigns of the Russian Empire against Khiva and Kokand, then left the army, moved to the village of Nanay, Yangikurgan district, Namangan region, and devoted the rest of his life to scientific research.
Keywords: Central Asia, M.Nalivkina, V.V.Bartold